2009
DOI: 10.1007/s10120-009-0505-z
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel chemotherapy for the treatment of gastric cancer

Abstract: cause of cancer mortality. Although the incidence of gastric cancer has been declining in most developed countries, esophago-gastric junctional tumor and tumor in the cardia has, conversely, been increasing [2] and these tumors still remain one of the biggest problems worldwide.The prognosis of patients with advanced (i.e., unresectable or metastatic) gastric cancer is very poor. The median survival time for such patients is 6 to 9 months [3]. For many years, various chemotherapeutic agents have been used in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 78 publications
1
71
0
Order By: Relevance
“…3 Previous studies 4,5 have demonstrated that systemic chemotherapy for palliation is advisable for this cohort to improve survival. Paclitaxel (PTX) is the most common hydrophobic, chemotherapeutic drug used in gastric cancer treatment, 6 but it also exhibits significant adverse effects because of the drug itself and the co-administered solvent. accumulate at tumor sites by incorporating targeting ligands on the nanoparticle surface.…”
Section: Introductionmentioning
confidence: 99%
“…3 Previous studies 4,5 have demonstrated that systemic chemotherapy for palliation is advisable for this cohort to improve survival. Paclitaxel (PTX) is the most common hydrophobic, chemotherapeutic drug used in gastric cancer treatment, 6 but it also exhibits significant adverse effects because of the drug itself and the co-administered solvent. accumulate at tumor sites by incorporating targeting ligands on the nanoparticle surface.…”
Section: Introductionmentioning
confidence: 99%
“…Peritoneal dissemination is still the most common pattern of recurrence even in patients who receive adjuvant chemotherapy, although adjuvant chemotherapy definitely improves overall survival [4][5][6]. Some chemotherapeutic drugs, such as paclitaxel, are considered to be effective for peritoneal metastasis because of the efficient peritoneal penetration from the blood [7]; however, most systemic chemotherapeutic agents are not effective for peritoneal recurrence because of the bloodperitoneum barrier. In this regard, intraperitoneal chemotherapy (IPC) can be considered as an additional adjuvant therapy for AGC.…”
Section: Introductionmentioning
confidence: 99%
“…80-23, revised 1996) and the institutional ethical guidelines for animal experiments. The mice were subcutaneously injected into the left axillary space with 0.1 ml of cell suspension containing 4-6x10 6 SGC-7901 cells. Seven days after implantation of tumor cells (when the tumor size was ~0.1-0.2 cm 3 ), mice were randomly divided into four groups (n=6) to receive different treatments.…”
Section: Flow Cytometry Analysis Equal Numbers Of Sgc-7901 Cells (1x10mentioning
confidence: 99%
“…As a standard anticancer drug, paclitaxel (PTX) serves a significant role in the treatment of a number of tumors. As reported in latest studies, the efficiency of single anticancer drug-paclitaxel reaches 11-23% in treating the gastric cancer of middle and advanced stages, while that of drug combination therapy is 50-60% (6). Harmine (HM), originally isolated from the seeds of Peganum harmala, is a tricyclic compound belonging to the β-carboline alkaloids.…”
Section: Introductionmentioning
confidence: 99%